Web2forDev: Linking civil society [SANGONet] - Barnard, David (Technical Centre for Agricultural and Rural Cooperation, 2007)
It started with two floppy disks smuggled into South Africa in the late 1980s. Today it continues to play a major role in promoting ICT in Southern Africa and now SANGONeT is looking to the future.